The Adaptation of Ciherang Rice Variety Roots to Various Levels of Low Nutrient Stress in Tidal Swamp Soils - Novisrayani Kesmayanti; Ruli Joko Purwanto; Evriani Mareza; Ummi Kalsum; Ilham Nur Zaman (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2023)
Rice cultivation in tidal land has many abiotic stresses. One of them is low nutrient stress. This research aims to determine and study the adaptation of rice roots to various levels of low nutrient stress in tidal swamp soil. These research was carried out from September 2016 to May 2017 at the Experimental Garden, Laboratory of Botany and Plant Physiology of Faculty of Agriculture of IBA University in Palembang, South Sumatra Province. These experiment used a Randomized Block Design with three replications and four low nutrient levels. The treatments are: N1 = 40% Fertilization dose (FD, N2 = 50% FD, N3 = 60% FD and N4 = 100% FD. The 100% FD is 300 kg urea. ha-1, 100 kg SP-36.ha-1 and 150 kg KCl.ha-1. These research used Ciherang rice varieties that planted in pots containing 12 kg of tidal swamp soil type B from Bunga Karang Village, Tanjung Lago District, Banyuasin Regency, South Sumatra Province, Indonesia. The results showed that low nutrient stress increased root length, root weight, root length density, root weight density, root weight ratio and number of tillers, but reduced crown weight and panicle weight per clump